Նոր Նախիջեւանի Չալթր գիւղի արձանագրութիւնները - Սահակյան, Արծրունի; Մանուչարյան, Աշոտ; Խաթլամաջյան, Հակոբ; Հարությունյան, Սասուն (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Большое армянское село Чалтырь — административный центр Мясникянского района Ростовской области Российской Федерации, населенный армянами. Известно, что его основали армяне-переселенцы из Крыма в Донской бассейн по указу императрицы Екатерины II (1762—1796) в 1778 году. Армянские надписи Донского региона, в том числе и села Чалтырь, в 1967 году собрал и в 1999 году включил в VII том «Свод армянских надписей» (Российская Федерация) Г. Григорян. The Armenian village of Chalter is a big village in Myasnikyan/Myasnikov region in Rostov-on-Don, Russian Federation. It is known that it was founded by the Armenians, who migrated from the Crimea, due to the order of Empress Catherine II (1762—1796) in 1778. The Armenian inscriptions of Don Region, as well as those of Chalter were collected by G. Grigoryan (in 1967) and afterwards were included in the “Book of Armenian Inscriptions” in 1999.
Keywords: Inscriptions; Epigraphy; History